Management of Acute Ischemic Stroke - Vanamoorthy, Ponniah; Samy, Kavu D.; Bidkar, Prasanna U. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Acute ischemic stroke (AIS) is a time-sensitive neurological emergency and it remains to be the most common type of stroke. Rapid neuroimaging is the cornerstone for initiating time-sensitive interventions in the treatment of AIS. Revascularization therapies that were once considered irreversible, including intravenous thrombolysis (IVT) and endovascular treatment (EVT), administered in a timely fashion have revolutionized the treatment of AIS. The indications for these therapies have expanded over the past few years and a lot of advancements are happening every year. IVT is offered to all eligible patients presenting within 3 hours of symptom onset and up to 4.5 hours with additional criteria. EVT with stent retrievers or aspiration devices, once limited to the first 6 hours of stroke onset, is now being offered up to 24 hours with advanced image-guided patient selection, which includes a computed tomography or magnetic resonance perfusion imaging. A protocol-based approach to the management of stroke, beginning from prehospital care reduces the time delay in the initiation of treatment. Providing access to these therapies by creating systems of care, hospital stroke team, and “stroke codes” improves the outcome of patients with AIS.
Keywords: stroke; acute ischemic stroke; intravenous thrombolysis; telestroke; CT perfusion